The Association Between Agility with Dribbling Performance Among Dasan Baru Putra East Lombok Football Players - Jamiludin; Dadang Warta Candra Wira Kesuma; Tiassari Janjang Suminar; Baiq Satrianingsih (Journal of Physical Education Health and Sport, 2026)
Agility is a key physical component in soccer. It supports the execution of technical skills, particularly dribbling. During dribbling, players must change direction rapidly, maintain balance, with coordinate body movements efficiently throughout the game. These abilities allow players to control the ball while responding to dynamic match situations. Despite its importance, empirical studies that examine the relationship between agility with dribbling ability in youth club players remain limited.These study aimed to examine the relationship between agility with dribbling performance among male soccer players in the Dasan Baru (DB) club in East Lombok. The research applied a correlational design with involved 20 male players as participants. Agility was assessed using the Illinois Agility Test. Dribbling performance was measured through a standardized soccer dribbling test. The collected data were analyzed using descriptive statistics to describe the characteristics of the variables. The Shapiro–Wilk test was used to examine data normality. The analysis then continued with Pearson product moment correlation to identify the relationship between agility with dribbling performance. The results revealed a statistically significant negative correlation between agility with dribbling performance (r = −0.71; p = 0.001). Players with higher agility levels completed the dribbling test in less time. The normality test showed that the data followed a normal distribution, which allowed the use of parametric statistical analysis. These findings indicate that agility has a meaningful association with dribbling performance in youth soccer players. Coaches should therefore include structured agility training in youth soccer development programs. Such training can help improve technical performance, particularly ball control with dribbling efficiency during play.